Application and mechanism study of EMD-Gel composite scaffold in dental pulp tissue repair - Gui, Luchen; Zhan, Peimeng; Zeng, Qian; Liang, Zhuoyao; Zou, Jiaxin; Guo, Jiang; Lin, Jiacheng (Frontiers in Bioengineering and Biotechnology, 2025)
This study developed an enamel matrix derivative-gelatin methacrylate (EMD-Gel) composite scaffold for functional dental pulp regeneration, addressing the limitations of traditional capping materials in inflammation control. The photo-crosslinked EMD-Gel exhibited a porous structure and sustained amelogenin release. In vitro, it promoted human dental pulp stem cell (hDPSCs) differentiation and inhibited inflammation. In vivo (rat pulp capping), EMD-Gel generated a continuous reparative dentin bridge of 213.3 ± 9.5 µm and exhibited substantially lower inflammatory infiltration than iRoot BP Plus, highlighting its advantages in both dentin bridge quality and inflammation resolution. Mechanistically, EMD-Gel synergistically activates the Wnt/β-catenin pathway and inhibits CCL2-MMP3-mediated inflammation. This material provides a novel, dual-functional platform for clinical pulp therapy.